Analisis Kausalitas Pengeluaran Pemerintah, Investasi, dan Tenaga Kerja Terhadap Produk Domestik Regional Bruto SWP Jember dan Sekitarnya - Nindya Eka Santi; Aisyah Jumiarti; Fivien Muslihatinningsih (UPT Penerbitan Universitas Jember, 2018)
RGDP is the total of all goods and services value which produced by all economics unit within a region. This study aims to determine the causality’s direction between government budget and RGDP, investment and RGDP, labor and RGDP, using panel data on RDU Jember and its regional area during 2000– 2014. The Granger causality test is used to identify the direction of the relationship between the variable between government budget and RGDP, investment and RGDP, labor and RGDP. The result of this study showed that there is a causal relationship between variables.Keywords: Granger causality, RGDP, government budget, investment, and labor